Community Empowerment Through Family Medicinal Plants (TOGA) - Iswanto Suwarno; Mi Jeong Choi; Keerththana Kumareswaran; Dawn Ching Tung Au; Jacqueline Aparecida Takahashi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Since the outbreak of Covid-19, the popularity of medicinal plants has increased. Strong immunity is believed to prevent yourself from being exposed to the virus outbreak. The community believes that using traditional medicines such as herbal medicine from ginger, turmeric, ginger or kencur can increase the body's immunity. Family medicinal plants (TOGA) are family (home) cultivated plants that have medicinal properties. TOGA planting can be done in pots or on the land around the house, and if the land planted is large enough then some of the crops can be sold and increase family income. Banjarharjo 1 is one of the hamlets in Muntuk Village, Dlingo District, Bantul Regency. Geographically, Muntuk Village is a village located in an area that is in the highlands. Communities in the village area generally still have a large yard of land. The results of field observations show that the current development of TOGA is more on the aspect of cultivation only with utilization that is not optimal and limited to oneself and one's family. Communities who already have knowledge about the efficacy of TOGA and master how to process it can cultivate medicinal plants individually and use them so that the principle of independence in family medicine will be realized. Especially during the Covid-19 pandemic, processing herbal medicine to maintain health with ingredients derived from their own plants will really help maintain economic stability as well. Based on an analysis of the problems faced by partners, several efforts can be made as a solution to empower the people of Banjarharjo 1 Village in increasing the use of TOGA in the Making of Herbal Medicine to Increase Body Immunity as a Prevention of Covid-19. This PKM activity was carried out using the method of observation, counseling, mentoring and demonstration of making herbal medicine from the TOGA plant. The application of technology begins with training partners in terms of introducing TOGA types, cultivation and planting methods, as well as processing/manufacturing TOGA products for CPOTB-based family medicines and herbs. In addition, training was also made on making good and attractive packaging. The partners of the Banjarharjo Village 1 PKK team who collaborated with the proposer provided active participation in the provision of existing places and facilities. The results of the activity showed that residents already had knowledge about how to plant TOGA, knew about the benefits of TOGA for maintaining health, as well as raised awareness among residents to grow medicinal plants around their homes and increased skills in processing herbal medicine from TOGA.